Challenges & Outcome of Thoracic Surgery in a Resource Constrained Developing African Country - Fadelelmoula, Tarig E.; Abdalla, Momen Mukhtar; Hussein, Husameldin Suliman (Current Respiratory Medicine Reviews, 2017)
Background: Thoracic surgeries have been safely applied to the surgical treatment of different thoracic conditions in our center since its introduction in September 2013. Our center is a small private center, with cardiothoracic unit as its main component, with only 20 beds, including 4 beds for the ICU. The ICU is well staffed and equipped. The hospital is supported with two operation rooms (OR), Clinical laboratory, Spirometry, Ultrasonography, Echocardiography, bronchoscopes and conventional X-Ray. The hospital doesn't have CT facility but it's done in a nearby diagnostic center when needed. This article summarizes and reflects our experience with thoracic surgery, highlighting the salient challenges and outcome. Methods: Retrospective description of cases, over a 3-year period (September 2013 to September 2016). All challenges and difficulties experienced during the course of patient care as well as complications and outcomes were recorded and analyzed. Results: Out of the 101 surgical operations performed in our hospital, during the study period, 87 (86%) were open thoracic surgeries. Patients were between the ages of 11 years and 67 years with a mean of 39 ± 9 years (95% confidence interval (CI)). Infective thoracic conditions were the most common indication for thoracic surgery in 45 patients (51.7%). Decortication for complicated pleural effusion was the most common thoracic surgery and was performed in 49 (59.5%) patients. Tumor resection was performed in 20 (22.9%) patients (Carcinoid tumors; 11 patients, Aspergillomas; in 5 patients and bronchial cancer; in 4 patients: 3 lobectomies & and 1 wedge resection). In 11 (12.6%) patient surgery was done to remove foreign bodies from different sites of the bronchial tree when removal with rigid bronchoscope was not possible. Penetrating chest stab wounds were repaired in 7 (8%) patients without complications. Major challenges experienced were patient late presentation to the hospital, non-availability of video assisted thoracic surgery (VATS) and positron emission tomography (PET) scan for proper staging and treatment of bronchial carcinoma. Complications included 5 deaths, 2 cases of post-operative bleeding and 2 cases of post-operative sepsis following decortication for empyema thoracic, hence the morbidity and mortality rates in our series of patients were 4.5% and 5.7%, respectively. Overall, 82 (94%) patients in our study experienced a positive outcome. Conclusion: This study highlighted the main obstacles which thoracic surgery service deals with in our hospital, as an example of a new private center in a resource-constrained setting. However, thoracic surgery is still safer in spite of the difficulties faced and complications are significantly low as compared to similar centers in the region.
Keywords: Challenges